2022
DOI: 10.1155/2022/1298692
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Vitamin C against Neomycin-Induced Apoptosis in HEI-OC1 Auditory Cell

Abstract: Ototoxic hearing loss results from hair cell death via reactive oxygen species (ROS) overproduction and consequent apoptosis. We investigated the effects of vitamin C (VC) on neomycin-induced HEI-OC1 cell damage, as well as the mechanism of inhibition. HEI-OC1 cells were treated with neomycin or with vitamin C (VC). The results indicated that VC had a protective effect on neomycin-induced HEI-OC1 cell death. Mechanistically, VC decreased neomycin-induced ROS generation, suppressed cell death, and increased cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…After chronic sciatic nerve constriction in rats, a functional imbalance between proapoptotic BAX and antiapoptotic BCL2 has been identified ( Maione et al, 2002 ). The decrease in the BAX/BCL2 ratio emphasizes the antiapoptotic effect of Cerebrolysin ( Lu et al, 2022 ), the antiapoptotic effect of local dexamethasone in agreement with previous studies ( Hoang et al, 2009 ; Lee et al, 2015 ), and the antiapoptotic effect of vitamin C to adapt or overcome Sciatic nerve injury ( Sourour et al, 2012 ; Gong et al, 2022 ). Similarly, the antiapoptotic effect of vitamin C was superior to Cerebrolysin and dexamethasone, which may be referred to as its ability in neutralizing free radicals and ameliorating oxidative stress-mediated cellular apoptosis and cell death.…”
Section: Discussionsupporting
confidence: 88%
“…After chronic sciatic nerve constriction in rats, a functional imbalance between proapoptotic BAX and antiapoptotic BCL2 has been identified ( Maione et al, 2002 ). The decrease in the BAX/BCL2 ratio emphasizes the antiapoptotic effect of Cerebrolysin ( Lu et al, 2022 ), the antiapoptotic effect of local dexamethasone in agreement with previous studies ( Hoang et al, 2009 ; Lee et al, 2015 ), and the antiapoptotic effect of vitamin C to adapt or overcome Sciatic nerve injury ( Sourour et al, 2012 ; Gong et al, 2022 ). Similarly, the antiapoptotic effect of vitamin C was superior to Cerebrolysin and dexamethasone, which may be referred to as its ability in neutralizing free radicals and ameliorating oxidative stress-mediated cellular apoptosis and cell death.…”
Section: Discussionsupporting
confidence: 88%
“…When TNF-α binds to the TNF receptor on the cell surface, the TNF receptor-related death domain induces the death-inducing signaling complex, which induces cell apoptosis. It has been reported that vitamin C suppresses TNF-α production (Chen et al 2014, Hartel et al 2004) and caspases, which are enzymes involved in the apoptosis cascade (Gong et al 2022, Perez-Cruz et al 2003. Thus, vitamin C supplementation to bovine PBMCs might suppress cells apoptosis by either decreasing TNF-α production or attenuating the apoptosis cascade.…”
Section: Discussionmentioning
confidence: 99%
“…This renders them a valuable tool for studying the molecular and cellular mechanisms underlying hearing loss and other auditory disorders. Neomycin is an aminoglycoside antibiotic that causes ototoxicity by generating toxic reactive oxygen species (ROS) in the inner ear hair cells [ 46 , 47 ] and induces cell death in HEI-OC1 cells [ 48 ]. To investigate its otoprotective effect, we confirmed the levels of cell viability afforded by the TS treatment applied to the neomycin-treated HEI-OC1 cells.…”
Section: Discussionmentioning
confidence: 99%